2014
DOI: 10.1111/tmi.12292
|View full text |Cite
|
Sign up to set email alerts
|

Toys and toilets: cross‐sectional study using children's toys to evaluate environmental faecal contamination in rural Bangladeshi households with different sanitation facilities and practices

Abstract: Abstractobjective To evaluate household faecal contamination using children's toys among 100 rural Bangladeshi households categorised as 'cleaner' (toilet that reliably separates faeces from the environment and no human faeces in/around living space) or 'less clean' (no toilet or toilet that does not reliably separate faeces from the environment and human faeces in/around living space).methods We distributed toy balls to each household and rinsed each study toy and a toy already owned by the household in 200 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 17 publications
3
47
1
Order By: Relevance
“…Furthermore, we provided sterile balls to children younger than five years from the same 360 households, encouraged them to play with the toys in their household settings for one day, rinsed them in 300 ml of sterile water and assayed the water for thermotolerant coliforms (Vujcic et al 2014).…”
Section: Handrinsesmentioning
confidence: 99%
“…Furthermore, we provided sterile balls to children younger than five years from the same 360 households, encouraged them to play with the toys in their household settings for one day, rinsed them in 300 ml of sterile water and assayed the water for thermotolerant coliforms (Vujcic et al 2014).…”
Section: Handrinsesmentioning
confidence: 99%
“…be associated with lower contamination of toy balls and hands. 26,41,42 Second, there are other routes of contamination, such as poor latrine cleanliness, presence of animal feces, or unsafe disposal of children's feces, that neither target household nor neighborhood sanitation access can prevent. There may also be important community-level social, geographical, cultural, and/or environmental factors that we did not capture in our study because we found that sentinel toys in Narshingdi district had a higher level of contamination compared with children's toys in Mymensingh district even after adjusting for potential confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…25 Sentinel toy ball rinse: Standard-sized (20 cm circumference) sentinel toy balls ( Figure 1) given to children to play with were collected after 24 hours and rinsed in a Whirl-Pak bag (19 × 38 cm) filled with 200 mL of Ringer's solution for 30 seconds following the methods used previously. 26 All samples were transported in a cool box to the icddr,b Environmental Microbiology Laboratory within 15-18 hours of collection, maintaining a temperature of 4-10°C.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the pervasive belief that child faeces are safe , unsafe disposal of child faeces increases exposure to faecal pathogens in the domestic environment . Infants and young children in LMIC are particularly vulnerable to microbial contamination in their environment through childhood mouthing behaviours during their exploratory stage of development and through contaminated outdoor play spaces . These exposures to faecal pathogens make them more susceptible to enteric infections resulting in diarrhoeal diseases .…”
Section: Introductionmentioning
confidence: 99%
“…Infants and young children in LMIC are particularly vulnerable to microbial contamination in their environment through childhood mouthing behaviours during their exploratory stage of development and through contaminated outdoor play spaces . These exposures to faecal pathogens make them more susceptible to enteric infections resulting in diarrhoeal diseases . A global meta‐analysis of child faeces disposal practices found that unsafe child faeces disposal was associated with a 23% increased risk of childhood diarrhoea , the second leading cause of death in children under 5 years of age .…”
Section: Introductionmentioning
confidence: 99%